PREVALENCE AND MOLECULAR CHARACTERISATION OF EIMERIA SPECIES IN COMMERCIAL CHICKENS IN OYO AND OGUN STATES, NIGERIA (2014)
Eimeria species are important coccidian parasites worldwide causing significant economic losses from clinical and subclinical coccidiosis in poultry. Vaccines for its control in Nigeria are imported without consideration of the local species often resulting in vaccine failure. This study determined the prevalence of and characterised the Eimeria species present in Oyo and Ogun States towards an effective control and prevention of coccidiosis. A semi-structured questionnaire was administered randomly to 166 poultry farmers (82, Oyo; 84, Ogun) based on the registered members of the Poultry Association of Nigeria, to obtain data on experience of coccidiosis and the prophylactic measures adopted. Poultry flocks were grouped into six epizootiological categories comprising: vaccinated and medicated 1-8 week-old (1, 2), vaccinated and medicated 9-18 week-old (3, 4) and above 19 week-old caged and deep-litter (5, 6). Pooled faecal samples were collected from 9, 9, 9, 20, 54, and 19 chicken flocks in Oyo and 9, 16, 18, 27, 39, and 12 in Ogun belonging to categories 1 to 6 respectively. Oocysts were isolated by modified flotation method, sporulated in 2.5% potassium dichromate and quantified by the McMaster method. Eimeria species were identified by morphometry, infection prevalence and relative abundance was determined. Eimeria DNA was extracted, amplified and quantified using Real-Time Quantitative Polymerase Chain Reaction (RTQPCR). Data were subjected to descriptive statistics, Chi-square, Student’s t and Kappa tests. Significance was set at p<0.05. Most of the respondents, 77 in Oyo; 69 in Ogun had experienced coccidiosis outbreaks, of which 74.2% and 71.6% were in below-8-week chicks. In Oyo and Ogun, 67.7% and 73.3% adopted vaccination; 32.3% and 26.7% adopted chemoprophylaxis while 37.1% and 21.9% reported outbreaks despite preventive measures. Oocyst burden was 49,494 and 2,830 oocysts-per-gram of faeces for cages and 71,585 and 8,255 for deep-litter in Oyo and Ogun respectively. Overall prevalence in Oyo was 65.0% (100.0%, 100.0%, 100.0%, 75.0%, 40.7% and 73.7%) and in Ogun, 61.2% (100.0%, 75.0%, 83.3%, 33.3%, 51.3% and 75.0%) in categories 1-6 respectively. Prevalence of 93.7% in chicks (100.0% in Oyo; 85.7% in Ogun) was significantly higher than the 55.7% (54.3% in Oyo; 56.9% in Ogun) for above 18 week-old. It was also significantly higher on deep-litter (73.7%, Oyo; 75.0%, Ogun) than in cages (40.7%, Oyo; 51.3%, Ogun). Species prevalences were; E. acervulina (100.0%, 83.3%), E. maxima (16.7%, 16.7%), E. necatrix (50.0%, 50%), E. tenella (66.7%, 66.7%) and E. mitis (50.0%, 66.7%) in Oyo and Ogun respectively. Relative abundance from morphometry were; Brunetti-Maxima (3.0%, 4.3%), Necatrix-Tenella-Praecox (45.0%, 23.6%) and Acervulina-Mitis (52.0%, 72.1%); from molecular characterization were; E. acervulina (48.0%, 20.0%), E. maxima (0.2%, 0.3%), E. necatrix (5.4%, 22.7%), E. tenella (20.2%, 13.5%) and E. mitis (25.5%, 43.5%) in Oyo and Ogun respectively. Comparison of RTQPCR results with tentative morphometric identification showed complete agreement in 77.8% (28 of 36) samples. Morphometry remains acceptable for routine tentative diagnosis; however, molecular characterisation is more precise for Eimeria species identification. The most prevalent species: E. acervulina, E. maxima, E. necatrix, E.tenella and E. mitis are therefore recommended for inclusion in coccidiosis vaccines.